Lady and the Tramp [videorecording (DVD)] - Luske, Hamilton S.; Geronimi, Clyde; Greene, Ward, 1892-1956 (Walt Disney signature collection., 2018)
A pedigreed cocker spaniel falls for the romance of a carefree mongrel, who helps her in her time of need.